Evaluación de la enzima tripanotión reductasa del parásito Trypanosoma cruzi frente a moléculas tipo carbenos N-Heterocíclicos empleando técnicas computacionales. - Melo Marquez, Angie (Universidad Antonio Nariño, 2024)
The Trypanosoma cruzi parasite is responsible for Chagas disease, mostly found in areas with scarce resources, which limits research focused on the development of non-toxic treatments for patients, in comparison with the drugs currently used: Nifurtimox and Benznidazole, which have adverse effects.